Cytogenotoxic and oxidative status evaluation of Morinda citrifolia - Moraes, Germano Pinho de (2016)
Cancer is one of the most leading causes of death worldwide. Morinda citrifolia was reported to have antitumor effects. Cisplatin (CDDP), Doxorubicin (DOX) and Cyclophosphamid (CPA) are the known effective chemotherapeutics, despite of having several side effects. This study evaluated antitumoral and oxidative effects of the aqueous extract of the fruit of M. critrifolia (AEMC) (15, 30, 60 and 120 µg/mL) in comparision to CDDP (1 and 5 μg/mL), CPA (20 μg/mL), DOX (2 μg/mL) and CPA + DOX (20:2 μg/mL) in Sarcoma 180 cells and Saccharomyces cerevisiae, respectively. Cytogenetic damage and DNA fragmentation were evaluated with cytokinesis-block micronucleus assay and comet assay, respectively. In addition, S. cerevisiae strains were used in oxidative damage evaluation. AEMC induced cytogenetic damage with the increased formation of micronuclei, nuclear buds and nucleoplasmic bridges compared to the antineoplastics tested. AEMC at 120 µg/ mL induced significant (p<0.05) DNA damage in Sarcoma 180 cells similar to the CDDP, as well as oxidative damage in S. cerevisiae strain deficient in mitochondrial superoxide dismutase (Sod2∆) and cytosolic catalase (Cat1∆). The bioactive compounds present in AEMC such as gallic, caffeic, chlorogenic, ellagic acid and rutin might be responsible for AEMC’s antitumoral activity.